Fatal trauma in a mummified shrew: Micro-CT examination of a little ancient Egyptian bundle. (December 2020) - Panzer, Stephanie; Nerlich, Andreas G.; Hutterer, Rainer; Bicker, Roxane; Schoske, Sylvia; Greinwald, Markus; Hollensteiner, Marianne; Augat, Peter
Graphical abstract: Highlights: Assessment of soft tissues helps to interpret skeletal trauma. The shrew suffered fatal head injury and spinal trauma. The mousetrap turned out to be the most probable tool to obtain the shrew. Apparently, the shrew was killed prior to the production of a votive mummy. This case represents a tessera in the knowledge of ritual practices of ancient Egypt. Abstract: Micro-computed tomography examination was used to identify the content of a little ancient Egyptian mummy bundle and to analyze pathologies and the cause of death. The bundle contained a complete shrew with preservation of the skeleton and soft tissues. The species of the adolescent shrew was classified as Crocidura religiosa . The skull revealed bilateral impression fractures of the skullcap indicating probably one hit on each side. The skull base was fractured and the left petrous bone broke out. The alignment of the spine was interrupted between the first and second thoracic vertebra resulting in a complete obstruction of the spinal canal and disconnection of the preserved spinal cord. The adjacent dorsal soft tissues of the shrew were markedly thickened and contained an irregularly bordered area that was filled with air. This finding was suggested to represent the residual cavity after haemorrhage that was replaced by air during the desiccation within the mummification process. This fatal spinal trauma was most probably caused by a mousetrap. After death, the shrew's body must have been effectively desiccated before wrapping with multiple textile layers. The procedure of capturing and killing of a shrew prior to the production of a votive mummy as described in this study represents a tessera in the knowledge of ritual practices within the ancient Egyptian animal cult.